Two Vernier-templated routes to a 24-porphyrin nanoring. - Kondratuk, D; Perdigao, L; O'Sullivan, M; Svatek, S; Smith, G; O'Shea, J; Beton, P; Anderson, H (2012)
Many hands make light work: Small templates working together have directed the formation of a giant π-conjugated macrocycle with a diameter of 10 nm-larger than many enzymes. The 24 porphyrin subunits of the nanoring are well resolved in the STM image. The conformation of the nanoring can be controlled by self-assembly of a stable 2:24 double-strand sandwich complex with 1,4-diazabicyclo[2.2.2]octane (DABCO). Copyright © 2012 WILEY-VCH Verlag GmbH and Co. KGaA, Weinheim.